Raising the Legal Age of Tobacco Sales: Policy Support and Trust in Government, 2014–2015, U.S. - Lee, Joseph G.L. (Am J Prev Med, 2016)
INTRODUCTION: IOM has called for an increase in the minimum age of tobacco product sales. It is not clear what age increase would garner the greatest public support, or whether trust in the U.S. government predicts policy support. METHODS: The data for these analyses are from a nationally representative telephone sample of U.S. adults (N=4,880) conducted from September 2014 to May 2015. The authors assessed whether support varied by the proposed minimum age of tobacco sales using a survey experiment (i.e., random assignment to the 19-, 20-, or 21-year age minimum condition), and, in cross-sectional analyses, whether smoking status, individual demographics, state-level politics, and general trust in the government predicted policy support. Analyses were conducted from May to December 2015. RESULTS: Odds of support for raising the minimum sales age to 21 years trended higher than support for raising to age 20 or 19 years (AOR=1.22, 95% CI=0.97, 1.53, p=0.09). There was majority support for raising the age of sales for cigarettes in all regions of the U.S. (66.3%, 95% CI=64.0, 68.6). Race, age, and trust in government were significant predictors of support. CONCLUSIONS: Raising the age of tobacco sales is broadly supported by the public. An age 21 years tobacco sales policy trends toward garnering more support than a policy at age 19 or 20 years. Trust in government may be an important consideration in understanding policy support beyond demographics.